The Effect of Profitability Ratio, Leverage, Company Size, and Audit Committee Gender Diversity on the Financial Performance of Sharia General Insurance Companies (2022-2024) - Qurrotinnurilzannah; Umi Suswati Risnaeni (Journal of Accounting and Finance Management, 2026)
This study aims to analyze the effect of profitability ratios, leverage, firm size, and audit committee gender diversity on the financial performance of Islamic general insurance companies in Indonesia. Financial performance is proxied by Return on Equity (ROE), profitability is measured using Return on Assets (ROA), leverage is measured by the Debt to Equity Ratio (DER), firm size is measured using the natural logarithm of total assets, and audit committee gender diversity is measured by the proportion of female members on the audit committee. This study employs secondary data obtained from the annual financial reports of Islamic general insurance companies during the period 2022–2024. The analytical method used is multiple linear regression with a panel data approach.The partial test results indicate that profitability (ROA), leverage (DER), firm size, and audit committee gender diversity do not have a significant effect on financial performance (ROE). In addition, the simultaneous test results show that all independent variables collectively do not have a significant effect on the financial performance of Islamic general insurance companies. The low Adjusted R² value indicates that the research model is not able to explain variations in financial performance adequately. These findings suggest that the financial performance of Islamic general insurance companies during the study period is influenced by factors other than the variables examined, such as macroeconomic conditions, industry regulations, and internal managerial factors. Therefore, future research is recommended to use a longer observation period, increase the sample size, and include other more relevant variables to obtain more comprehensive results.